Network effects, compatibility decisions, and horizontal product differentiation - Bernd Woeckener (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 1999)
This paper analyzes decisions on (in)compatibility and product design of two competing hardware suppliers in the presence of network effects. We show that they either establish compatibility and differentiate their variants strongly or maintain incompatibility and locate their variants at the center of the consumer distribution. In the latter case, a 'standards war' takes place. Moreover, we show that a commitment to compatibility becomes more attractive for suppliers when it can be done before product designs are fixed because then, it can significantly soften competition in locations. Considering welfare, it turns out that standards wars can be welfare superior to compatibility.
urn:nbn:de:bsz:21-opus-21408
Keywords: L12; L13; L15; 330; Computerindustrie; Normung; Network Externalities; Duopol; Produktdifferenzierung; Wohlfahrtseffekt; Theorie